Determinación de prevalencia de piroplasmosis en equinos de paso colombiano mediante frotis sanguíneo - Pazmiño Cedeño, Lisbeth Melisa (2023)
In order to determine the prevalence of piroplasmosis in Colombian Paso equines in Portoviejo canton, Manabí province, Ecuador, an investigation was carried out in 7 Colombian Paso equine farms located in the parishes of Mejía, Colón, Playa Prieta and Picoazá. A total of 66 equine blood samples were randomly collected. The samples were evaluated through the blood smear method and the Wright staining technique, to identify the relationship between the variables farm, age, sex and sector, the Chi-square test was obtained at the 95% confidence level. The results found indicate that 20 Colombian Paso equines positive for piroplasmosis were detected in Portoviejo canton, for a general prevalence of 30.3 %. The highest percentage of prevalence occurred in horses older than 13 years, which correspond to 60%. Regarding the sector, a higher prevalence was shown in the Colón and Mejía parishes with 47.1%; 33.3% respectively, associated with high populations of tick vectors of the causative agents, derived from contact with cattle. However, the prevalence of equine piroplasmosis in Portoviejo canton is indistinct depending on the gender, sector, age range or the location of the equine kennels evaluated. It is concluded that Portoviejo canton, Manabí province, is prevalent to equine piroplasmosis in the sampled areas during the study period.